7m=11-5m-2=2m-9

Simple and best practice solution for 7m=11-5m-2=2m-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m=11-5m-2=2m-9 equation:



7m=11-5m-2=2m-9
We move all terms to the left:
7m-(11-5m-2)=0
We add all the numbers together, and all the variables
7m-(-5m+9)=0
We get rid of parentheses
7m+5m-9=0
We add all the numbers together, and all the variables
12m-9=0
We move all terms containing m to the left, all other terms to the right
12m=9
m=9/12
m=3/4

See similar equations:

| 3.9(12.1r-6.3)=75.6 | | 4(7x+8)=-19 | | -2x-(x+3)=12 | | (4x-5/3)=1 | | 4y-7y=8+7 | | 3.14r^2=8 | | 1.5x*17=x | | 0=-16t^2+92t-100 | | 4c=4^4c+2 | | |2x-9|+4=5 | | 2x/3-8=×+7 | | 9x-8=-4 | | 49−−√=x | | 9x+9=-9 | | 4x^2+23x+40=0 | | x+1/3x+1/4x=2 | | 2b=19-√12,25-9,5 | | 20x-8=18x+12 | | 2+c=3 | | x=√4+3 | | √4=x | | 6x+3/x=11 | | 3y+2×=19 | | 4=36x-10 | | 2x/3-9=×+7 | | ¹¹√(2x+3)=4x+7 | | 7-4(x-2)=12(3x-9) | | 7-4x+8=36-108 | | 3x+10=50x+20 | | 3x+10=50+20 | | 3x+39=-3 | | -11.3=r+2.7 |

Equations solver categories